1993
DOI: 10.1111/j.1365-2133.1993.tb15144.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblotting of streptococcal antigens in guttate psoriasis

Abstract: Guttate psoriasis may be precipitated by acute streptococcal infection, usually of the upper respiratory tract. We have studied the immune response to streptococci in 26 patients presenting with a first or recurrent episode of acute guttate psoriasis (AGP), using immunoblotting. Eighteen of 26 patients studied had a demonstrable response to a wide range of streptococcal antigens using this approach, compared with 14 of 26 patients who demonstrated a response using more conventional antistreptococcal antibody t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The activation of the alternative complement pathway and cross‐reactivity between streptococcal M protein surface antigens and human epidermis may be associated with the initiation of clinical manifestation 18,19 . Clinical studies suggest that a clear history of upper respiratory infection was obtained in 19.2–86%, 2,14,20,21 and serological evidence of recent streptococcal infection was found in 54–93% 1,2,18–21 . In our study, history of previous upper respiratory infection were found in 20 of 36 patients (55.6%) and elevation of ASO titers in 23 (63.9).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…The activation of the alternative complement pathway and cross‐reactivity between streptococcal M protein surface antigens and human epidermis may be associated with the initiation of clinical manifestation 18,19 . Clinical studies suggest that a clear history of upper respiratory infection was obtained in 19.2–86%, 2,14,20,21 and serological evidence of recent streptococcal infection was found in 54–93% 1,2,18–21 . In our study, history of previous upper respiratory infection were found in 20 of 36 patients (55.6%) and elevation of ASO titers in 23 (63.9).…”
Section: Discussionsupporting
confidence: 46%
“…18,19 Clinical studies suggest that a clear history of upper respiratory infection was obtained in 19.2-86%, 2,14,20,21 and serological evidence of recent streptococcal infection was found in 54-93%. 1,2,[18][19][20][21] In our study, history of previous upper respiratory infection were found in 20 of 36 patients (55.6%) and elevation of ASO titers in 23 (63.9). Williams et al 8 suggested that guttate psoriasis occurring after the streptococcal infection was a common preceding manifestation of chronic plaque psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the antigens of S. pyogenes recognized by the sera of psoriatic patients, Wilson et al 22 . studied by Western blot the response patterns of the sera of patients with guttate psoriasis and healthy subjects to streptococcal antigens of groups A, C and G. They did not find bands or patterns specific for any of the groups examined, but the guttate psoriatic group had both heavier and more numerous bands.…”
Section: Discussionmentioning
confidence: 99%
“…In this field, the most convincing evidence has been reported in the setting of the guttate type, which has been related to streptococcal pharyngeal infection on the basis of epidemiological and immunological studies, including the T-cell receptor specificities of lesional skin-infiltrating T cells [10,11,12,13,14]. Likewise, a case control study had suggested that recent pharyngeal infection was associated with a 7-fold increase in the risk of a first episode of guttate psoriasis compared with controls, but the study did not provide any information on the identification of infectious agents [15].…”
Section: Discussionmentioning
confidence: 99%